1996
DOI: 10.2337/diacare.19.5.435
|View full text |Cite
|
Sign up to set email alerts
|

Raised Serum Sialic Acid Concentration Precedes Onset of Microalbuminuria in IDDM: A 10-year follow-up study

Abstract: UAER and serum sialic acid concentration increase coincidentally before the onset of persistent microalbuminuria. An increased serum sialic acid concentration is predictive for the onset of microalbuminuria independent of age, sex, diabetes duration, smoking, blood pressure, vWF, and total HDL cholesterol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 22 publications
0
15
1
1
Order By: Relevance
“…There are several possible explanations for these discrepant findings. First, studies that found high vWf levels to be associated with the development of elevated UAER 8 had a shorter duration of follow-up (3.1 to 5.3 years) than did studies that did not find this association (Yokoyama et al 29 and the present study, 6.6 to 10.0 years). Late-onset elevated UAER may have a different pathogenesis than does early-onset elevated UAER.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…There are several possible explanations for these discrepant findings. First, studies that found high vWf levels to be associated with the development of elevated UAER 8 had a shorter duration of follow-up (3.1 to 5.3 years) than did studies that did not find this association (Yokoyama et al 29 and the present study, 6.6 to 10.0 years). Late-onset elevated UAER may have a different pathogenesis than does early-onset elevated UAER.…”
Section: Discussioncontrasting
confidence: 47%
“…28 Our findings on CRP support the hypothesis that low-grade inflammation is causally related to the development of elevated UAER. 15,29 The main stimulators of production of acute-phase reactants are proinflammatory cytokines. Interleukin-6 may be an important mediator of mesangial cell proliferation and matrix overproduction 30 but also of an increase in general vascular permeability without involvement of the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients with microalbuminuria, for example, have quite advanced renal structural changes, and microalbuminuria may here be a marker of microvascular damage that has already occurred. If circulating sialic acid increases before microangiopathy develops (33), it may be an early signal of processes such as hypercytokinemia that cause or drastically increase the risk of vasculopathy.…”
Section: Conclusion -mentioning
confidence: 99%
“…It is likely that endothelial dysfunction and chronic low-grade inflammation, presumably provoked by hyperglycemia, precedes a slight elevation of UAE, leading to "microalbuminuria" [32][33][34] . However, endothelial dysfunction as well as chronic lowgrade inflammation was mostly studied by serum/ plasma concentrations, such as von Willebrand factor, tissue-type plasminogen activator, soluble vascular cell adhesion molecule 1, sialic acid and C-reactive protein [32][33][34] , while we investigated endothelial dysfunction through measurement of brachial artery FMD. Our finding of the close association between FMD and microalbuminuria, together with the findings of the above serum markers reported previously, indicates a close linkage between endothelial dysfunction and microalbuminuria, which may be an attractive explanation for the fact that microalbuminuria is a risk marker of CVD in diabetes.…”
Section: Fmd and Microalbuminuriamentioning
confidence: 99%